DYNAMIC MODEL OF UPPER EXTREMITY AND ITS APPLICATION: A SYSTEMATIC REVIEW - Saad, S.; Ibrahim, N.; Osman, N.A.A. (2023)
Dynamics models are widely used in analyzing kinematics and kinetics analysis. Dynamic modeling and simulation can be useful in estimating the torques/forces produced in the limb during various motions, as well as any potential dangers. The aim of this research is to examine the method that is preferable in analyzing the dynamic model of the upper extremity and its application. Several methods have been identified and widely used in analyzing the dynamic model of the upper extremity such as Kane’s method, Lagrange method, optimization method, regression method and many more. Kane's approach, on the other hand, is most commonly used to analyze 3D arm segments due to its advantages which is a vector-based approach. The Lagrange approach is suitable to use when the potential and kinetic energy of a system could be easily identified. Meanwhile, most of the researchers used statistical analysis to verify their model and calculation. However, it could be difficult to replicate the simulation work of others because some were not publicly available. Thus, it was recommended to choose a reference from prior studies that will serve as guidance for researchers to solve relevant issues in this field.